2023
DOI: 10.3390/ijms24020945
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Celiac Disease Treatment

Abstract: Celiac disease (CD) is a common autoimmune disease affecting around 1% of the population. It consists of an immune-mediated enteropathy, triggered by gluten exposure in susceptible patients. All patients with CD, irrespective of the presence of symptoms, must endure a lifelong gluten-free diet (GFD). This is not an easy task due to a lack of awareness of the gluten content in foods and the extensive incorporation of gluten in processed foods. Furthermore, a GFD imposes a sense of limitation and might be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 130 publications
0
13
0
Order By: Relevance
“…The 0.5-mg dose showed an effect on exploratory endpoints including a 26% decrease in celiac disease patient-reported outcome symptomatic days ( p = 0.017), a 31% increase in improved symptom days ( p = 0.034), a 50% or more reduction from baseline of the weekly average abdominal pain score for 6 or more of 12 weeks of treatment ( p = 0.022), and a decrease in the non-gastrointestinal symptoms of headache and tiredness ( p = 0.010). However, in 2022 a phase 3 clinical trial was suspended after an interim analysis showed no significant effectiveness [ 21 ]. More high-quality data are needed to consider this molecule for possible adjunctive therapies in CD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 0.5-mg dose showed an effect on exploratory endpoints including a 26% decrease in celiac disease patient-reported outcome symptomatic days ( p = 0.017), a 31% increase in improved symptom days ( p = 0.034), a 50% or more reduction from baseline of the weekly average abdominal pain score for 6 or more of 12 weeks of treatment ( p = 0.022), and a decrease in the non-gastrointestinal symptoms of headache and tiredness ( p = 0.010). However, in 2022 a phase 3 clinical trial was suspended after an interim analysis showed no significant effectiveness [ 21 ]. More high-quality data are needed to consider this molecule for possible adjunctive therapies in CD.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, a plethora of phase-II trials have been recently published or are ongoing with promising results [ 21 ]. Unfortunately, today no novel, effective therapies are available for the treatment of CD and RCD.…”
Section: Introductionmentioning
confidence: 99%
“…This process is mediated by a key tight junction modulator–zonulin. Production of zonulin is induced–mainly–by bacteria overgrowth and gluten that binds to receptor CXCR3 in erythrocytes ( Fasano, 2020 ; Machado, 2023 ). On the other hand, zonuline activates tight junction relaxation, causing the delivery of gliadin peptides to lamina propria.…”
Section: Celiac Disease Novel Therapiesmentioning
confidence: 99%
“…First and foremost, adherence to a GFD presents substantial challenges for many CD patients. The scarcity of suitable gluten-free alternatives, the higher cost of these products, and the inherent challenges of maintaining strict dietary regimens over extended periods make compliance arduous [93]. In fact, the adherence rates of a GFD among CD patients vary widely, ranging between 42% and 91%, and in many cases, less than 50% of patients maintain this regimen consistently [94].…”
Section: Novel Therapiesmentioning
confidence: 99%